GENETIC DIVERSITY ANALYSIS OF GREEN GRAM (VIGNA RADIATA (L.) WILCZEK.) - U. A. GARJE; M. S. BHAILUME; D. R. NAGAWADE (The Bioscan, 2013)
Forty genotypes of green gram used to study the nature and magnitude of genetic divergence using Mahalanobis’s D2 Statistics. The data for ten important quantitative traits recorded from the genotypes raised in Randomized Block Design having three replications. The forty Green gram genotypes were grouped into thirteen clusters. Cluster III was largest with ten genotypes followed by cluster II with eight genotypes. The maximum inter-cluster distance was observed between cluster VIII and IV, suggesting that the genetic architecture of the genotypes in one cluster differ entirely from those included in other clusters. Three characters viz. Seed yield per plant (g), No. of pod per plant, and Pod length (cm) contributed maximum in manifestation of genetic diversity. Seed yield per plant had maximum Phenotypic and Genotypic Coefficient of Variation (PCV and GCV), followed by number of pods per plant. High magnitude of heritability (broad sense) was recorded for number of pod per plant. High heritability coupled with high genetic advance was observed for plant height and number of pod per plant suggesting that, the role of additive gene effect and possibilities of achieving high genetic progress through selection. The genotypes KM-09-152, KM-09-156, KM-09-183, BM-2005-1, Vaibhav, KM-09-187, KM-09-173 and KM-09-158 were identified as genetically diverse parents, which can be utilized for future crop improvement programme